2022
DOI: 10.3390/jcm11020331
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Surgical Treatment Algorithm for Unstable Syndesmotic Injuries

Abstract: Background: Surgical treatment of unstable syndesmotic injuries is not trivial, and there are no generally accepted treatment guidelines. The most common controversies regarding surgical treatment are related to screw fixation versus dynamic fixation, the use of reduction clamps, open versus closed reduction, and the role of the posterior malleolus and of the anterior inferior tibiofibular ligament (AITFL). Our aim was to draw important conclusions from the pertinent literature concerning surgical treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 164 publications
0
4
0
1
Order By: Relevance
“…First, this study evaluated the translation of the fibula in the coronal and sagittal directions as the laxity of syndesmosis, but not in fibula rotation. Markus et al demonstrated that an unstable AITFL should be repaired and augmented, as it represents an important stabilizer of external rotation of the distal fibula [22]. Given those ligament injuries of the ankle generally occur from the anterolateral side in clinical situation, fibula laxity in the external rotation can occur in the early stages of ligament injury, compared to the appearance of coronal and sagittal laxity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, this study evaluated the translation of the fibula in the coronal and sagittal directions as the laxity of syndesmosis, but not in fibula rotation. Markus et al demonstrated that an unstable AITFL should be repaired and augmented, as it represents an important stabilizer of external rotation of the distal fibula [22]. Given those ligament injuries of the ankle generally occur from the anterolateral side in clinical situation, fibula laxity in the external rotation can occur in the early stages of ligament injury, compared to the appearance of coronal and sagittal laxity.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study evaluated the translation of the ibula in the coronal and sagitdirections as the laxity of syndesmosis, but not in ibula rotation. Markus et al demonstrated that an unstable AITFL should be repaired and augmented, as it represents an important stabilizer of external rotation of the distal ibula [22].…”
Section: Discussionmentioning
confidence: 99%
“…J. Litrenta et al в своем рандомизированном контролируемом исследовании также подтвердили негативное влияние повреждения дистального синдесмоза на результаты хирургического лечения переломов лодыжек [21]. Во многих случаях для устранения повреждений и восстановления функции пораженного сустава необходимо хирургическое вмешательство, что в настоящее время является приоритетным методом лечения данной патологии [7,[22][23][24]. Проведено множество исследований, сравнивающих различные варианты хирургических вмешательств, например, мета-анализ A. Grassi et al на тему динамического и статического методов фиксации дистального синдесмоза, доказавший преимущество динамических видов фиксации над статическими [22].…”
Section: гений ортопедии 2024;30(1)unclassified
“…At the same time, concomitant repair of unstable syndesmosis injuries does not have a unified approach. Here, the most common divergence of views on surgical treatment is associated with the use of two conceptually different methods-screw fixation of the syndesmosis and elastic (dynamic) fixation [11]. Injuries of the tibiofibular syndesmosis are among the most difficult in surgical treatment.…”
Section: Introductionmentioning
confidence: 99%